The crucible of co-production: Case study interviews with Recovery College practitioner trainers. (December 2019) - Dalgarno, Mark; Oates, Jennifer
Objectives: This study explored healthcare professionals' accounts of being practitioner trainers in a mental health Recovery College, where they worked with peer trainers, who were people with lived experience of mental illness, to co-produce workshops for mental health service users and staff. The aim of this study was to understand the process of co-production in the Recovery College from the perspective of practitioner trainers. Design: Single-site case study. Setting: A Recovery College in the South of England, open to staff and service users from one mental health care provider organisation. Methods: Semi-structured interviews with eight mental healthcare professionals. Transcripts were thematically analysed. Results: A central image of 'the workshop as crucible' emerged from the three themes derived from the analysis. Co-facilitating the workshop was a 'structured' encounter, within which health professionals experienced 'dynamism' and change. For them, this involved experiences of 'challenge and discomfort'. Conclusion: Findings from this study contribute to the evidence base for the evaluation of Recovery Colleges by focusing on the training impact on staff. Findings suggest that taking on a trainer role in Recovery College co-production is beneficial for healthcare professionals as well as mental health service users, especially if healthcare professionals are open to the dynamism and possible discomfort of these workshop encounters. Future research, however, should expand beyond single-site case studies to test the extent to which this metaphor and themes are appropriate to describing the 'transformative' element of co-production.